Memory Awareness in Nursing Home Residents - McDougall, Graham J. (Gerontology, 1998)
BACKGROUND: Health care providers often believe that individuals with cognitive disturbance are unaware of their deficits. The term unawareness was first used to describe hemiplegia following right hemisphere stroke but has since been applied to unawareness of any neurological or neuropsychological deficit. Clinicians usually rely on their subjective observations to evaluate the patient’s awareness of deficits, and few investigators have systematically evaluated this important clinical phenomenon. OBJECTIVE: The aim of this study was to compare cognition, depression, health, and metamemory (capacity, change, locus, and strategy) in four groups of nursing home residents: the cognitively impaired (29%), depressed (18%), mixed with both cognitive impairment and depression (32%), and controls (21 %). METHODS: Subjects were 106 residents of six nursing homes between the ages of 79 and 87 with a mean age of 84.18 (SD = 10.01) years, and an average of six comorbid medical conditions. Cognitive function was measured with the Mini Mental State (MMSE); depression with the Geriatric Depression, and metamemory with the Meta-memory in Adulthood scales. Anyone scoring <15 on the MMSE was excluded. Subjects included 31 with cognitive impairment, 19 depressed, 34 mixed, and 22 controls. RESULTS: In this sample, 61% were cognitively impaired; however, only 12 had a diagnosis in their records indicating cognitive disturbance. Forty-three percent were depressed. The correlations between depression and capacity (r = −0.38), change (r = −0.50), and locus (r = −0.25) were significant. The controls were significantly younger than the cognitively impaired group. The controls also had higher perceived health status scores than either the cognitively impaired or the depressed group. However, the mixed group’s perceived health status scores were significantly higher than the depressed group’s scores. CONCLUSION: The metamemory components of capacity and change were able to differentiate the cognitively impaired from the mixed group. Information on the etiology of cognitive impairment was not available since residents’ charts in the six nursing homes provided inadequate documentation and incomplete diagnostic histories. Therefore, quantitative methods for examining memory awareness and the affective state of elderly patients is important for clinicians in order to make informed treatment decisions.